The moral imagination : the art and soul of building peace - Lederach, John Paul (Oxford University Press, 2005)
John Paul Lederach's has provided consultation and direct mediation in a range of situations from the Miskito/Sandinista conflict in Nicaragua to Somalia, Northern Ireland, the Basque Country, and the Philippines. Peacebuilding, in his view, is both a learned skill and an art.